2012
DOI: 10.1530/jme-11-0064
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of naturally occurring transglutaminase 2 mutants implicated in early-onset type 2 diabetes

Abstract: Transglutaminase 2 (TG2) is an enzyme with diverse biological functions. TG2 catalyzes transamidation reactions, has intrinsic kinase activity, and acts as a G-protein in intracellular signaling. TG2 (Tgm2)-null mice are glucose intolerant and have impaired glucose-stimulated insulin secretion (GSIS). Furthermore, three naturally occurring missense mutations in the human TGM2 gene, corresponding to amino acid substitutions of Met330Arg, Ile331Asn, and Asn333Ser in the TG2 protein, have been reported and found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
9
1
1
Order By: Relevance
“…Our data, however, are contrary to prior reports implicating a role for TG2 in insulin secretion [3], [18][21]. One of these studies [3] used mixed-strain TG2 −/− mice generated independently by another group [5].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our data, however, are contrary to prior reports implicating a role for TG2 in insulin secretion [3], [18][21]. One of these studies [3] used mixed-strain TG2 −/− mice generated independently by another group [5].…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, it is possible that unexpected contributions from the 129 genome that interact deleteriously with the B6 genome might explain the glucose tolerance and impaired insulin secretion reported by Bernassola et al ., (2002) using their mixed-strain TG2 −/− mice. Another study [21] recently reported impaired insulin secretion by islets isolated from that same TG2 −/− mouse line, now reported to be on a B6 background, although the number of generations of backcrossing and, thus, the genomic homogeneity of the line was not stated. Other studies implicating transamidase activity in insulin secretion [18][20] have used small molecule inhibitors such as methylamine, cystamine and dansylcadaverine, which, in addition to being alternate substrates that competitively inhibit transglutaminases [36], are well-known to have many biological effects, including antioxidant activity, inhibition of a range of cysteine proteases, as well as inhibition of endocytosis [37]–[39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the ATP binding to ssDacA , ssDacA DGA , and ssDacA RHR , an ATP-Sepharose binding assay was used in a binding procedure previously described with minor modifications (Dias et al, 2009;Reese and Boothroyd, 2011;Bai et al, 2012;Salter et al, 2012). Briefly, purified recombinant proteins and bovine serum albumin, used as negative control, were incubated at 4°C for 1 h with a 50-mL bed volume of g-linked ATP-Sepharose (Innova Biosciences, Cambridge, UK) in 50 mM Tris, pH 7.5, and 150 mM NaCl, respectively.…”
Section: Atp Binding Assaymentioning
confidence: 99%
“…TG2 has been reported to be a candidate gene for MODY, with heterozygous mutations that impair transamidase activity (M330R, I331N, or N333S) having been identified in one or more affected individuals from three different families (Bernassola et al 2002b;Porzio et al 2007). In vivo (Bernassola et al 2002b) and less convincing in vitro (Salter et al 2012) studies have reported impaired glucose-stimulated insulin secretion by pancreatic islets from TG2 À/À mice [(De Laurenzi and Melino 2001), mixed-strain 129-B6 or B6, respectively] relative to wild-type mice. However, another study (performed according to the recommended guidelines for animal husbandry and study design), using congenic B6 and 129 TG2 À/À lines [ (Nanda et al 2001) backcrossed 12 generations to the respective inbred strains], showed no impairment in vivo or in vitro of glucose-stimulated insulin secretion by pancreatic islets from TG2 À/À mice relative to wild-type littermates .…”
Section: Diabetesmentioning
confidence: 99%